Metafora „cybergrzechu” jako inspiracja do refleksji nad pokusami Sieci - Siwicki, Marek; Galanciak, Sylwia (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Cyfrowa rzeczywistość musi mieć realne odbicie w działalności wychowawczej i kształcącej, zaś nauczyciel powinien stać się aktywnym uczestnikiem procesu dostrzegania, nazywania i definiowania nowych zjawisk towarzyszących dzisiejszej edukacji. Świadomość konsekwencji, jakie może nieść ze sobą nadmierne zanurzenie dziecka w cyberprzestrzeni, jest niezwykle ważnym elementem intelektualnego wyposażenia przyszłych wychowawczyń najmłodszych. Artykuł odpowiada m.in. na pytanie: Jak problem ten widzą studentki pedagogiki oraz jak przyszłe wychowawczynie interpretują i definiują „cybergrzechy”?

Digital reality must have a real reflection in educational and teaching activities, and the teacher should become an active participant in the process of perceiving, naming and defining new phenomena that accompany today’s education. The awareness of the consequences that an excessive involvement of a child in cyberspace may bring is an extremely important element of the intellectual armament of children’s future educators. The article answers, among others, the following questions: how is this problem perceived by pedagogy female students and how do the future educators interpret and define “cybersins”?
The Metaphor of „Cybersin” as an Inspiration to Reflect on the Temptations of the Web
Keywords: sieć; internet; cybergrzechy; cyfrowa rzeczywistość; youthquake; studentki pedagogiki; network; cybersins; digital reality; pedagogy students